(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The author examines some judgments by national and supranational Courts about ethically sensitive issues. He offers his opinions about the fundamental role of the dialogue between Courts, arguing that the European Court of Human Rights has been gradually influencing the decisions of national Courts.